Small and Medium Enterprises across the Globe : A New Database - Ayyagari, Meghana; Beck, Thorsten; Demirguc-Kunt, Asli (World Bank, Washington, DC, 2014)
This paper describes a new cross-country database on the importance of small and medium enterprises (SMEs). This database is unique in that it presents consistent and comparable information on the contribution of the SME sector to total employment and GDP across different countries. The dataset improves on existing publicly available datasets on several grounds. First, it extends coverage to a broader set of developing and industrial economies. Second, it provides information on the contribution of the SME sector using a uniform definition of SMEs across different countries, allowing for consistent cross-country comparisons. Third, while we follow the traditional definition of the SME sector as being part of the formal sector, the new database also includes the size of the SME sector relative to the informal sector. This paper describes the sources and the construction of the different indicators, presents descriptive statistics, and explores correlations with other socioeconomic variables.